Value-at-risk, informativeness of earnings. - Lim, Benjamin Wan Heng. (2008)
Our paper examines the relationship between S&P500 firms’ 10-K market risk disclosures in terms of Value-at-risk (VaR), mandated by SEC Financial Reporting Release No.48 in 1997, and the informativeness of earnings. Our results show that earnings informativeness decrease with the increasing magnitude of the VaR figures disclosed.